2022
DOI: 10.1093/cid/ciac724
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Diseases Society of America Guidelines on the Treatment and Management of Patients With COVID-19 (September 2022)

Abstract: Background There are many pharmacologic therapies that are being used or considered for treatment of coronavirus disease 2019 (COVID-19), with rapidly changing efficacy and safety evidence from trials. Objective Develop evidence-based, rapid, living guidelines intended to support patients, clinicians, and other healthcare professionals in their decisions about treatment and management of patients with COVID-19. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
196
2
6

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(206 citation statements)
references
References 262 publications
2
196
2
6
Order By: Relevance
“…Prior studies have reported a high mortality rate of SOTRs with COVID‐19 in the prevaccine era, ranging from 18% to 24% 1–4 . The lower death rate in our not fully vaccinated group may have been due to the inclusion of partially vaccinated patients in this group as well as improved treatments for COVID‐19 including postexposure monoclonal antibodies and anti‐inflammatory therapies such as tocilizumab and baricitinib 25 . Importantly, all COVID‐19‐related deaths in our study were in unvaccinated patients.…”
Section: Discussionmentioning
confidence: 73%
“…Prior studies have reported a high mortality rate of SOTRs with COVID‐19 in the prevaccine era, ranging from 18% to 24% 1–4 . The lower death rate in our not fully vaccinated group may have been due to the inclusion of partially vaccinated patients in this group as well as improved treatments for COVID‐19 including postexposure monoclonal antibodies and anti‐inflammatory therapies such as tocilizumab and baricitinib 25 . Importantly, all COVID‐19‐related deaths in our study were in unvaccinated patients.…”
Section: Discussionmentioning
confidence: 73%
“…18 However, several guidelines for COVID-19 treatment suggest that antibiotics should not be routinely prescribed. [19][20][21] From the real-world clinical settings in Taiwan, COVID-19 patients often present as febrile with respiratory symptoms, such as fever, dry cough, dyspnea, and associated chest X-ray changes, as reported in other countries. 10,22,23 It is difficult for clinicians to differentiate COVID-19 patients with and without concurrent bacterial infections at admission.…”
Section: Discussionmentioning
confidence: 97%
“…The diagnosis, defining severity, and management of COVID-19 was modified according to the available recommendations by the Infectious Diseases Society of America and the National Institutes of Health during the pandemic. 15,16 All patients were followed throughout their hospital stay. Outcomes were recorded as the time required for resolution of DKA, in-hospital death or survival, and length of hospital stay (days).…”
Section: Methodsmentioning
confidence: 99%